Wet Lab-Based Cataract Surgery Training Curriculum for the PGY 2/PGY 3 Ophthalmology Resident - Seth M. Pantanelli; George Papachristou; Christine Callahan; Michael Chen; Yousuf Khalifa (Association of American Medical Colleges, 2018)
Introduction Studies have shown that structured cataract surgery training curricula are beneficial for resident surgeons-in-training, yet nearly one-third of US training programs do not have one, and public dissemination of said curricula are lacking. Methods We created a microsurgical simulation center and accompanying structured training curriculum. Weekly lectures focused on the steps of cataract surgery, variations on technique, and complications. Each didactic was followed by a 1.5- to 2-hour time block with faculty supervision in the wet lab. Finally, to demonstrate proficiency, residents submitted a recorded video illustrating their competency within 1 week of the lecture. We reviewed videos and provided written feedback via a standardized form. Curriculum effectiveness was evaluated through formative feedback on the course itself and complication rates for resident-performed cataract surgery before and after implementation of the curriculum. Results The course was implemented in 4 consecutive academic years, allowing time for nine junior residents to participate in the course at least once before operating as a senior. The incidence of posterior capsule tears for senior residents decreased from 3.07% in the 4 years preceding curriculum implementation to 1.13% for the senior residents who completed the course at least once as juniors (p = .0571). Supervised wet lab sessions and submitted videos allowed faculty to identify surgically struggling residents early. Discussion Implementation of a cataract surgery training curriculum for junior ophthalmology residents provides a safe and effective environment to practice surgical techniques. Such a curriculum may decrease the complication rates of beginner surgeons.